2015
DOI: 10.1007/s00701-015-2451-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient characteristics support unfavorable psychiatric outcome after treatment of unruptured intracranial aneurysms

Abstract: The current study demonstrates an increased rate of positive pre-interventional psychiatric histories in the iA collective. Although those patients represent only a small subgroup, they still may play an important role concerning the overall outcome after iA treatment. Early detection and psychological support in this subgroup might help to improve the overall outcome. Further studies are needed to evaluate the influence of this new aspect on the multifactorial etiology of unfavorable psychiatric outcome after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 47 publications
1
10
1
Order By: Relevance
“…With respect to personality in patients with UIAs, the study conducted in the Netherlands noted high levels of neuroticism in these patients and a history of previous mental disorders. These results suggest that such precursors could be associated with the low HRQoL levels shown and with the differences found with the comparison group [14][15][16]. However, the study does not establish a relationship between personality traits and the mediation of patient symptomatology, as also found in this study.…”
Section: Plos Onecontrasting
confidence: 66%
See 2 more Smart Citations
“…With respect to personality in patients with UIAs, the study conducted in the Netherlands noted high levels of neuroticism in these patients and a history of previous mental disorders. These results suggest that such precursors could be associated with the low HRQoL levels shown and with the differences found with the comparison group [14][15][16]. However, the study does not establish a relationship between personality traits and the mediation of patient symptomatology, as also found in this study.…”
Section: Plos Onecontrasting
confidence: 66%
“…It should be noted that the high prevalence of emotional disturbance in people with UIAs may be associated with personality factors. A previous study reported higher levels of neuroticism and very low levels of openness in patients with UIAs compared to patients with meningioma [14,15]. Secondary analyses of this same study indicated that 37.8% of patients with data collection and analysis, decision to publish, or preparation of the manuscript.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Endovascular coiling and surgical clipping both bear similar risk ratios regarding death, bleeding, cerebral ischemia, and functional independence at daily activities for unruptured intracranial aneurysms [4]. However, differences in cognitive outcome measures for patients after clipping compared to endovascular treatment were described [3,5,21]. Especially patients with incidental aneurysms bear a relatively high burden of pre-interventional psychiatric symptoms [5].…”
Section: Discussionmentioning
confidence: 99%
“…Both clipping and coiling are widely accepted therapeutic approaches and obviously bear different procedural risks. However, some studies have indicated that patients undergoing surgery are more likely to suffer from impaired cognition and from neuropsychiatric symptoms such as anxiety and depression [5]. A recent study identified postoperative delayed paradoxical depression following surgical repair of unruptured intracranial aneurysms in around 10% of patients, which may be comparable to mild posttraumatic stress disorder and resulted in a reduced rate of patients fully returning to their activities of daily life [6].…”
Section: Introductionmentioning
confidence: 99%